Inverse method for the reconstruction of contact stress in point contact with surface profile measurement. (1st August 2022) - Lin, Q; Sun, C; Chen, J
Abstract: Based on the boundary element method (BEM) and surface profile measurement, a method is developed to solve the inverse problems with point contact. The missing contact stress is modeled by six contact parameters. Using the BEM, the contact parameters are related to the surface profiles after deformation. The contact parameters is optimized with a global optimization algorithm by minimizing the difference between the modeled and measured surface profiles. A numerical example is adopted to evaluate the accuracy of the proposed method as well as its robustness against the noises introduced to the surface profiles. Subsequently, the inverse method is used for the reconstruction of the contact stress in the point contact. The agreement between the reconstructed results and the applied load validates the effectiveness of the inverse method in engineering practice.